INFLUENCE OF RE-PLANTED MOSS PLANT ON SOIL FERTILITY (Scientific journal of the Fergana State University, 2025)
Root and leguminous residues of leguminous crops enrich the soil with organic matter, slightly improve the conditions of humification and mineralization by chemical composition, provide optimal soil nutrition, improve its physicochemical properties.